Radar-climatology of Delhi and neighbourhood : Convective cells of the hot weather season (MAUSAM, 1965)
The paper presents a radar--climatological analysis of the cell-census for Delhi and neighbourhood based on the New Delhi radar data for the hot weather seasons of 1958, 1959 and 1960. The object is to investigate the various characteristics of the echo cells, The study covers cell-diameters, cell-spacings, their distributions, variations with the progress of the season, their inter-relationships,  height-diameter relationships, etc.